REMOVAL OF BRETTANOMYCES BRUXELLENSIS FROM RED WINE USING MEMBRANE FILTRATION. Issue 5 (25th April 2012) - UMIKER, N.L.; DESCENZO, R.A.; LEE, J.; EDWARDS, C.G.
Abstract : ABSTRACT: While sulfites help limit growth of the spoilage yeast, Brettanomyces, SO2 has been reported to decrease cell size, thereby potentially decreasing the porosities of filtration membranes required for removal. Brettanomyces bruxellensis strains B1b and F3 were inoculated into red wines and after 12 days, half of the wines received ≈0.5 mg/L molecular SO2 prior to filtration on day 20. Strain B1b was retained by filtration through 1.2 µm membranes from wines with or without SO2 . In contrast, two of three filtration replicates of wines inoculated with F3 exhibited growth approximately 40–50 days after filtration through the same porosity. However, this strain was removed from wines using 0.8 µm membranes. Results indicate that Brettanomyces may enter a "viable‐but‐not‐culturable" physiological state upon exposure to SO2 . While culturability and morphology of B. bruxellensis was affected by SO2 exposure, this factor did not impact removal of this yeast by membrane filtration. PRACTICAL APPLICATIONS: Cells of B. bruxellensis have been observed to decrease in size upon exposure to sulfites (SO2 ), thereby possibly affecting filtration recommendations for its removal from red wines. Though culturability on plate count agar and microscopic morphology was influenced by SO2, use of membrane filters with porosities ≤0.8 µm removed the spoilage yeast from red wines. In those situations where a larger membrane porosity is desired, additional SO2 must be added to curtail potential spoilage by cells of Brettanomyces that pass through the filtration medium.